2017
DOI: 10.1038/srep39904
|View full text |Cite
|
Sign up to set email alerts
|

IFN type I and II induce BAFF secretion from human decidual stromal cells

Abstract: B cell activating factor (BAFF) is a critical cytokine for maturation of immature B cells. In murine lymph nodes, BAFF is mainly produced by podoplanin-expressing stromal cells. We have previously shown that circulating BAFF levels are maximal at birth, and that farmers’ children exhibit higher BAFF levels in cord blood than non-farmers’ children. Here, we sought to investigate whether maternal-derived decidual stromal cells from placenta secrete BAFF and examine what factors could stimulate this production. W… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 24 publications
(13 citation statements)
references
References 64 publications
1
12
0
Order By: Relevance
“…Among the general leukocyte populations, decidua basalis contained more B cells, monocytes, and CD56 dim NK cells, whereas parietalis was comprised of more T cells, NKT-like cells, and CD56 bright NK cells. This pattern is in general in line with previous publications examining decidual immune cell subsets [ 19 22 ].…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Among the general leukocyte populations, decidua basalis contained more B cells, monocytes, and CD56 dim NK cells, whereas parietalis was comprised of more T cells, NKT-like cells, and CD56 bright NK cells. This pattern is in general in line with previous publications examining decidual immune cell subsets [ 19 22 ].…”
Section: Discussionsupporting
confidence: 92%
“…Although B cells have generally been ignored in the context of decidual immunology, their presence has been demonstrated in previous publications both by flow cytometry [ 20 , 22 , 29 , 30 ] and by immunohistochemistry [ 31 ]. We have previously shown that DSCs from both decidua basalis and parietalis readily produce B cell-activating factor of the tumor necrosis factor family (BAFF) after stimulation with interferons [ 22 ], suggesting a role for B cell maturation in the decidua. We found that the frequency of B cells was higher in basalis compared to parietalis, but that parietalis contained a higher proportion of mature/naïve B cells at the expanse of transitional B cells.…”
Section: Discussionmentioning
confidence: 99%
“…These cells are the primary source of B-cell activating factor (BAFF), a critical cytokine for peripheral B-cell maturation [80]. In the placenta, BAFF is produced by podoplanin-positive decidual stromal cells stimulated by inflammatory cytokines, such as interferon (IFN)- or IFN-α, and IFN-γ stimulation increases the number of decidual stromal cells expressing podoplanin [81]. Thus, podoplanin may be important for regulating immune responses in the placenta during inflammation; however, whether or not podoplanin is directly involved in BAFF secretion or B-cell homeostasis is unknown.…”
Section: Podoplanin and The Immune Responsementioning
confidence: 99%
“…BAFF plays a role in determining insulin resistance [10][11][12] and has been implicated in GDM. BAFF is an essential immune regulator that was recently reported to be secreted by the placenta [6,13].…”
Section: Introductionmentioning
confidence: 99%